Purifikasi Anggota Dewan Perwakilan Daerah Pasca Putusan Mahkamah Konstitusi No. 30/PUU-XVI/2018 - M. Yasin Al Arif; Hasanuddin Muhammad (Jurnal Konstitusi, 2020)
In the representation system, the Regional Representative Assembly (DPD) has an important role to articulate regional interests in state and government practices. Therefore, the DPD has an equal position with the DPR. This paper aims to determine the implications of the Constitutional Court's decision No. 30/PUUXVI/2018 on electoral developments in Indonesia especially the general election of DPD members which is limited to two main issues. First, what are the legal implications of the Constitutional Court's decision No. 30/PUU-XVI/2018 on the nomination of DPD and, second, what is the urgency of affirming DPD RI Members to be free from members of political parties? The results of the study indicate that the legal implications arising after the issuance of the Constitutional Court's decision No. 30/PUU-XVI/2018 happened to change the mechanism of registration of candidates for election candidates for DPD members and the urgency of affirming DPD members to be free from political parties is to avoid double representations and to strengthen the principle of checks and balances between the DPD and the DPR.